2015
DOI: 10.1155/2015/171306
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside-Rb1 Protects Hypoxic- and Ischemic-Damaged Cardiomyocytes by Regulating Expression of miRNAs

Abstract: Ginsenoside (GS-Rb1) is one of the most important active compounds of ginseng, with extensive evidence of its cardioprotective properties. However, the miRNA mediated mechanism of GS-Rb1 on cardiomyocytes remains unclear. Here, the roles of miRNAs in cardioprotective activity of GS-Rb1 were investigated in hypoxic- and ischemic-damaged cardiomyocytes. Neonatal rat cardiomyocytes (NRCMs) were first isolated, cultured, and then incubated with or without GS-Rb1 (2.5–40 μM) in vitro under conditions of hypoxia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…Rb1 also protected against myocardial ischemia injury via the enhanced expression of eNOS [76]. These initial findings lead to follow-up investigations concerning whether Rb1 could protect neonate rat cardiomyocytes from hypoxia/ischemia (HI) oxygen (10%) induced damage using either a preconditioning or co-exposure protocol [79][80][81]. The HI experimental study utilized a six-hour preconditioning period followed by a 12 h HI exposure period.…”
Section: Heart: Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rb1 also protected against myocardial ischemia injury via the enhanced expression of eNOS [76]. These initial findings lead to follow-up investigations concerning whether Rb1 could protect neonate rat cardiomyocytes from hypoxia/ischemia (HI) oxygen (10%) induced damage using either a preconditioning or co-exposure protocol [79][80][81]. The HI experimental study utilized a six-hour preconditioning period followed by a 12 h HI exposure period.…”
Section: Heart: Cardiomyocytesmentioning
confidence: 99%
“…The HI experimental study utilized a six-hour preconditioning period followed by a 12 h HI exposure period. Rb1, which was tested over a concentration range of 3-160 µM, demonstrated a biphasic concentration response with protection being optimized at 40 µM, dropping significantly off from 80-160 µM ( Figure 17) [80]. An assessment of five MiRNA, at the optimal Rb1 concentration (i.e., 40 µM) revealed that three MiR (Mir-1, Mir 29a, and Mir 208) were markedly increased.…”
Section: Heart: Cardiomyocytesmentioning
confidence: 99%
“…Previous studies have only identified differentially expressed miRNAs in OGD-injured NRCMs with GS-Rb1 treatment (12,13). The present study is the first to verify the miRNA target of GS-Rb1 in the OGD induced cardiomyocytes apoptosis.…”
Section: Discussionmentioning
confidence: 59%
“…Culture of neonatal rat cardiomyocytes (NRCMs) from heart tissues. Primary cultures of NRCMs from a total of 180 12-24 h-old male Sprague Dawley rats (weight range, 5-6 g; Laboratory Animal Center, Jilin University, Changchun, China) were prepared through gentle serial trypsinization, as described previously (12)(13)(14). All animal protocols were approved by the Animal Care Center and Use Committee of Jilin University (Changchun, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation